Cloning of the mouse hepatitis virus (MHV) receptor: expression in human and hamster cell lines confers susceptibility to MHV. - Dveksler, G S (1991)
The cellular receptor for murine coronavirus mouse hepatitis virus (MHV)-A59 is a member of the carcinoembryonic antigen (CEA) family of glycoproteins in the immunoglobulin superfamily. We isolated a cDNA clone (MHVR1) encoding the MHV receptor. The sequence of this clone predicts a 424-amino-acid glycoprotein with four immunoglobulinlike domains, a transmembrane domain, and a short intracytoplasmic tail, MHVR1 is closely related to the murine CEA-related clone mmCGM1 (Mus musculus carcinoembryonic antigen gene family member). Western blot (immunoblot) analysis performed with antireceptor antibodies detected a glycoprotein of 120 kDa in BHK cells stably transfected with MHVR1. This corresponds to the size of the MHV receptor expressed in mouse intestine and liver. Human and hamster fibroblasts transfected with MHVR1 became susceptible to infection with MHV-A59. Like MHV-susceptible mouse fibroblasts, the MHVR1-transfected human and hamster cells were protected from MHV infection by pretreatment with monoclonal antireceptor antibody CC1. Thus, the 110- to 120-kDa CEA-related glycoprotein encoded by MHVR1 is a functional receptor for murine coronavirus MHV-A59.